On the Dynamic Extent of Delimited Continuations - Biernacki, Dariusz; Danvy, Olivier; Shan, Chung-chieh (BRICS Report Series, 2005)
We show that breadth-first traversal exploits the difference between the static delimited-control operator `shift’ (alias `S’) and the dynamic delimited-control operator `control’ (alias `F’). For the last 15 years, this difference has been repeatedly mentioned in the literature but it has only been illustrated with one-line toy examples. Breadth-first traversal fills this vacuum.